International Competition, Productivity Change and the Organisation of Production - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1986)
The modern manufacturing firm competes with product quality improvements rather than cost efficient production of simpler products. R&D spending, marketing, availability of spare parts and service facilities, customs designs, etc. embody the product quality enhancing process, requiring considerable knowledge transfer and making information processing in a broad sense a major manufacturing activity. We can talk of a shift from a base in cost efficient processing to a product technology base, in which producers grow closer to their customers through internalizing part of the market process previously handled by independent traders. The important competition parameters are product innovations, which account for the bulk of measured R&D spending and marketing. In European firms, and in European firms based in small but advanced industrial countries in particular, the latter make up the bulk of foreign activities. Foreign activities are sizeable compared to the entire domestic manufacturing sector in countries like the Netherlands, Sweden and Switzerland. Marketing through foreign establishment is a product quality raising factor, but also a means of climbing trade barriers.
Keywords: D21; D24; F60; L20; 330; Product quality; R&D; globalisation; firm specific knowledge; micro-to-macro model; Multinationales Unternehmen; Internationaler Wettbewerb; Produktivität; Schweden